2021
DOI: 10.1021/acsinfecdis.1c00539
|View full text |Cite
|
Sign up to set email alerts
|

Allosteric Inhibition of Acinetobacter baumannii ATP Phosphoribosyltransferase by Protein:Dipeptide and Protein:Protein Interactions

Abstract: ATP phosphoribosyltransferase (ATPPRT) catalyzes the first step of histidine biosynthesis in bacteria, namely, the condensation of ATP and 5-phospho-α-D-ribosyl-1-pyrophosphate (PRPP) to generate N 1 -(5-phospho-β-D-ribosyl)-ATP (PRATP) and pyrophosphate. Catalytic (HisG S ) and regulatory (HisZ) subunits assemble in a hetero-octamer where HisZ activates HisG S and mediates allosteric inhibition by histidine. In Acinetobacter baumannnii, HisG S is necessary for the bacterium to persist in the lung during pneum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 6 publications
(40 citation statements)
references
References 47 publications
2
38
0
Order By: Relevance
“…28 AbHisZ was produced as previously reported. 26 All PaHisGS mutants were expressed and purified by the same protocol as PaHisGS. 28 Partial charges for the ligand PRPP, were calculated in vacuo at the HF/6-31G* level of theory using Gaussian 16 Rev.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…28 AbHisZ was produced as previously reported. 26 All PaHisGS mutants were expressed and purified by the same protocol as PaHisGS. 28 Partial charges for the ligand PRPP, were calculated in vacuo at the HF/6-31G* level of theory using Gaussian 16 Rev.…”
Section: Discussionmentioning
confidence: 99%
“…and PaHisGS share 43% and 69% sequence identity with their orthologues from the pathogenic bacterium Acinetobacter baumannii, AbHisZ and AbHisGS, respectively, but PaHisZ has been shown to be a potent allosteric inhibitor of AbHisGS. 26 We thus hypothesised that AbHisZ could inhibit WT-PaHisGS. However, addition of AbHisZ activated catalysis by WT-PaHisGS (Fig.…”
Section: Allosteric Activation Of Wt-and R56a-pahisgs By An Orthologo...mentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have reported identifying potential drug targets in A. baumannii by the subtractive proteomics approach [ 20 , 21 , 22 , 49 ]. Some of the 68 shortlisted drug targets in the current study have been reported in previous studies [ 20 , 21 , 22 , 50 , 51 , 52 , 53 ]. However, it is worth mentioning that our study is the first one to proceed with further in vitro and in vivo validation.…”
Section: Discussionmentioning
confidence: 99%